Internuclear ophthalmoplegia of abduction: clinical and electrophysiological data on the existence of an abduction paresis of prenuclear origin. - Thömke, F (1992)
Three patients showed unilateral and five bilateral abduction paresis. Five had associated adduction nystagmus of the contralateral eye. Electrophysiological testing of masseter and blink reflexes indicated an ipsilateral rostral pontine or mesencephalic lesion, and excluded a lesion of the infranuclear portion of the abducens nerve. Abduction paresis was attributed to impaired inhibition of the tonic resting activity of the antagonistic medial rectus muscle. The prenuclear origin of the disorder is based on morphological and neurophysiological evidence of an ipsilateral inhibitory connection between the paramedian pontine reticular formation and the oculomotor nucleus running close to but separated from the medial longitudinal fasciculus.